Impacto de diferentes vias de contaminação por mercúrio inorgânico sobre os biomarcadores de estresse oxidativo, a função cardio-respiratória e o potencial de bioconcentração e biomagnificação em matrinxã, Brycon amazonicus (Spix & Agassiz, 1829) e em traíra, Hoplias malabaricus (Bloch, 1794) - Monteiro, Diana Amaral (2011)
Both the mercury (Hg) and their compounds are recognized as important pollutants, because they are persistent, bioaccumulative and toxic. The largest sources of mercury pollution are chloride-alkaline industry and gold mining. The growing contribution of Hg in aquatic environments results in high accumulation of mercury in fishes tissue and their consumers, which poses a serious risk to humans and ecosystems. The aim of this study was to evaluate the effects of acute exposure (96 hours), via water, and a sub-chronic exposure (30 days), via food, to sub-lethal doses of inorganic mercury (HgCl2) in two species Brazilian fishes ecologically distinct, matrinxã (Brycon amazonicus) and traíra (Hoplias malabaricus). The cardiorespiratory responses to normoxia (140 mmHg) and graded hypoxia (120 - 10 mmHg), cardiac contractility in vitro, biomarkers of oxidative stress and the potential for bioconcentration and biomagnification were analyzed. The results show that exposure of these species to HgCl2 induces oxidative stress in different tissues, limiting the maintenance of cardiac contractility by reducing the force of myocardial contraction and modulates the response pattern of cardio-respiratory variables to graded hypoxia front, making the species more susceptible to environmental variations of O2. Regarding matrinxã specifically, the critical points highlighted were mainly severe oxidative stress in heart and white muscle; marked reduction of contraction force of isolated heart muscle; hyperventilation and increase the value of the critical tension of O2 in more than 100%; and intense bioconcentration in all tissue whose values exceeded the maximum allowed. In the case of traíras the results were: oxidative stress in the liver and gills; hypoventilation; decreased in metabolic rate and O2 extraction; and bradycardia with impaired electrical conduction as first degree atrioventricular block and lengthiness of the potential plateau action of cardiac muscle. Therefore, the data indicate that mercury via food or water and in environmentally relevant concentrations, can have a negative impact on behavior, health, performance and success of the species, making their survival and/or vulnerable populations.